Legal mobilization dilemmas in the Nordics – an autoethnographic reflection on the role of scholars in the asylum commission - Lundberg, Anna (Frontiers in Sociology, 2024)
The present article investigates key dilemmas in collective legal mobilization initiatives in the field of asylum and migrants’ rights. Focusing on my own experiences from working in the Asylum Commission – a trans-sectional mobilization initiative that ran in Sweden from 2019 to 2022, involving researchers, civil society representatives, and professionals – I analyze two central dilemmas that characterized our work. First, I consider how we collectively struggled for the legal right to asylum and through this struggle also reproduced injustices and potential border control harms which are embedded in asylum regulations. Second, I analyze how the Commission strived to provide a knowledge-based account of the consequences of legislative changes post the long summer of migration in 2015 that would have an impact on future legislation, while simultaneously taking an open stand in solidarity with people who were excluded from the legislative process; i.e., asylum seekers. The article underlines the need for sociolegal research that highlights ways to address dilemmas in legal mobilization work and offers empirical insights from collective mobilization for migrants’ rights in a Northern European country.